A Matter of Public Concern: The Case for Academic Freedom Rights of Public University Faculty. Issue 1 (29th November 2020) - Park, Michael K.
Abstract : Although the Supreme Court of the United States has described academic freedom as a "special concern, " the Court has never recognized a First Amendment right of academic freedom reserved for the professoriate. Legal disputes involving scholarship and classroom speech have overwhelmingly favored institutions over individual academics. However, the lack of uniformity and inconsistent application of the current public speech framework to academia speaks to the uneasiness of applying general public employee speech principles to academic speech. This article addresses how Supreme Court jurisprudence has shaped the arc of academic freedom toward an institutional right, and how the current public employee speech framework has displaced academic speech protection tied to scholarship and teaching. Finally, the article offers both descriptive and normative arguments, including a functional theory of academic freedom and the Madisonian-Meiklejohnian conception of the First Amendment, to make the case for constitutional consideration of speech pursuant to scholarship and teaching.